2007
DOI: 10.3386/w13399
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of Banks in Japan: Causes and Consequences

Abstract: We appreciate valuable comments from Andy Rose, Taka Ito, Hiro Ito, Barry Williams, and other participants at the NBER-EASE eighteenth annual conference. 266 Kaoru Hosono, Koji Sakai, and Kotaro Tsuru 1. City banks and regional banks are both corporations licensed under Bank Law, while shinkin banks are cooperatives of small-and medium-sized enterprises (SMEs) licensed under Shinkin Bank Law. Regional banks are classified into first-tier and second-tier regional banks according to the associations they belong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…In a study of distressed and non-distressed German bank mergers, Koetter et al (2007) found that the financial performance of banks engaging in M&As is poor relative to regulator-ratings. Similar results were found by Hosono et al (2006) for Japan, where cost-and profit-inefficient banks were most likely to engage in M&A activity. Goddard et al (2009) use a hazard function approach to investigate consolidation in the US credit union industry between 2001 and 2006.…”
Section: Geographic Diversificationsupporting
confidence: 90%
See 1 more Smart Citation
“…In a study of distressed and non-distressed German bank mergers, Koetter et al (2007) found that the financial performance of banks engaging in M&As is poor relative to regulator-ratings. Similar results were found by Hosono et al (2006) for Japan, where cost-and profit-inefficient banks were most likely to engage in M&A activity. Goddard et al (2009) use a hazard function approach to investigate consolidation in the US credit union industry between 2001 and 2006.…”
Section: Geographic Diversificationsupporting
confidence: 90%
“…A study of hypothetical large Canadian bank mergers using data from 1976 to 1996 revealed potentially large scale economy benefits (McIntosh 2002). Hosono et al (2006) studied Japanese bank mergers and found evidence of substantial post-merger cost and profit efficiency gains, although the capital positions of the merging banks tended to weaken.…”
Section: Post-merger Performance Outside the Usmentioning
confidence: 98%
“…Shinkin banks are generally smaller than city banks and tier 1 and tier 2 regional banks and larger than credit cooperatives (shinyo kumiai). Shinkin banks have a significant role in the development of SMEs in different regions and in achieving comprehensive growth throughout Japan (Hosono, Sakai, and Tsuru 2006). Shinkin banks provide 14.7% share of total loans to SMEs having a total of ¥128 trillion (equivalent to $1,244 billion) in funds (Shinkin Central Bank 2014).…”
Section: Development Of Specialized Private Banks For Sme Financingmentioning
confidence: 99%
“…12;2013 technological capability: credit unions with no website were at the highest risk of acquisition. Hosono, Sakai and Tsuru (2006) investigated the motives and consequences of the consolidation of cooperative banks in Japan during the period 1984-2002. They reached three major findings: 1) less profitable and less cost-efficient banks are more likely to be an acquirer and a target, though even less profitable and less efficient banks are more likely to be a target rather than an acquirer.…”
Section: Motivations Underlying the Realization Of Mergers And Acquismentioning
confidence: 99%